Implementation of differentiated learning with a Culturally Responsive Teaching approach to increase students' interest in learning - Irfan Saninur Azis; Siti Dewi Maharani; Vinencia Ika Indralin (Elementary Teacher Education Program, Majalengka University, 2024)
Implementing learning aligned with the Culturally Responsive Teaching (CRT) approach is a method enabling a more accurate comprehension and representation of knowledge, tailored to students' individual learning tendencies and styles, while considering the diverse cultures surrounding them. Transitioning from the old paradigm to adopting learning in accordance with the demands of the 21st century and the current curriculum is imperative, despite the uneven distribution of the Independent Curriculum across schools. This study is prompted by students' lack of interest in learning, evident in their limited engagement in the learning process. The objective of this research is to illustrate the impact of employing differentiated learning with a Culturally Responsive Teaching (CRT) approach on enhancing students' learning interest. The research methodology employed was classroom action research conducted over two cycles. The research process was executed collaboratively, employing a lesson study approach and utilizing qualitative descriptive methods, with data collection techniques comprising observation and questionnaires. Research findings demonstrate an increase in students' learning interest through the implementation of differentiated learning with a Culturally Responsive Teaching (CRT) approach. This is evidenced by the average N-Gain value for learning interest in Cycle I, which was 0.4029, classified as medium, and in Cycle II, it reached 0.7014, classified as high. Thus, differentiated learning integrating the Culturally Responsive Teaching (CRT) approach has been proven highly effective in establishing a more inclusive and meaningful learning atmosphere within the classroom